(untitled) - Inlander, Charles B. (New York, 1995)
Encompassing a wealth of basic information--such as finding the right specialist, filing a complaint, questioning a doctor's procedures--a comprehensive handbook designed for the consumer demystifies the bureaucratic and technical aspects of the health care system.
Keywords: Y học, thường thức,Medicine, popular; Handbooks, manuals, etc; Sổ tay, hướng dẫn sử dụng, vv